48.7k views
3 votes
PLEASE ITS URGENT I NEED HELP!!! I BEG YOU GUYS PLEEAASEEE THANKS..

PLEASE ITS URGENT I NEED HELP!!! I BEG YOU GUYS PLEEAASEEE THANKS..-example-1
User Gouthamsa
by
5.6k points

1 Answer

2 votes

b,c\text{ and d}

Step-by-step explanation

remember some properties of the exponents


\begin{gathered} a^m\cdot a^n=a^(m+n) \\ (a^m)^n=a^(m\cdot n) \\ a^(-m)=(1)/(a^m) \end{gathered}

then, to solve this solve each option and compare

Step 1


6^(-5)\cdot6^2

solve


\begin{gathered} 6^(-5)\cdot6^2=6^(-5+2)=6^(-3) \\ \end{gathered}

so, this is not an answer

Step 2


((1)/(6^2))^5

solve


\begin{gathered} ((1)/(6^2))^5=(6^(-2))^5=6^((-2\cdot5))=6^(-10) \\ \end{gathered}

so, this is an answer

Step 3


\begin{gathered} (6^(-5))^2 \\ \text{solve} \\ (6^(-5))^2=6^(-5\cdot2)=6^(-10) \end{gathered}

so, this is an answer

Step 4


\begin{gathered} (6^(-3))/(6^7) \\ \text{solve} \\ (6^(-3))/(6^7)=(1)/(6^3\cdot6^7)=(1)/(6^(3+7))=(1)/(6^(10))=6^(-10) \end{gathered}

so, this is an answer

Step 5


\begin{gathered} (6^5\cdot6^(-3))/(6^(-8)) \\ \text{solve} \\ (6^5\cdot6^(-3))/(6^(-8))=(6^(5-3))/(6^(-8))=(6^2)/(6^(-8))=6^2\cdot(1)/(6^(-8))=6^2\cdot6^8=6^(10) \end{gathered}

so, this is not an answer

I hope this helps you

User Lakota
by
5.0k points